Fungicidas sistêmicos para ferrugem do cafeeiro: controle e eficiência na mistura com cúpricos e fertilizantes foliares - Vilela, Ximena Maira de Souza (2019)
The use of fungicides is the main method to control coffee rust in susceptible cultivars. The ideal management is done using fungicides on soil and leaves. The soil treatment must be applied preventively due to the time required for the product to be absorbed and translocated from the roots to the leaves. The disease and weather conditions should be monitored for the application of foliar fungicides. The tank mix has been widely used in Brazil for spraying and aims to optimize time and cost and reduce soil compaction. The mixes can undergo additive, synergistic or antagonistic actions that can affect the efficiency of disease control. Therefore, the objective of this paper was to evaluate the efficiency of fungicides triazole and strobilurin mixed with foliar fertilizer and copper fungicides to control coffee rust in the field and determine their effect on defoliation and crop productivity. The behavior of different active principles applied via soil was evaluated regarding the rust incidence on seedling physiology and also the productive coffee trees during two consecutive harvests. All experiments were organized in randomized blocks with four replicates. The foliar fungicide treatments evaluated were 1) Control, consisting of a foliar fertilizer; 2) Azoxystrobin + Cyproconazole mixed with copper fungicide and foliar fertilizer; 3) Azoxystrobin + Cyproconazole applied separately; 4) Cyproconazole mixed with copper fungicide and foliar fertilizer; 5) Cyproconazole applied separately; 6) Azoxystrobin mixed with copper fungicide and foliar fertilizer; 7) Azoxystrobin applied separately, and 8) Copper fungicide and foliar fertilizer. The rust incidence, defoliation, productivity, pH and electrical conductivity of the spray solution were measured. The soil fungicide treatments consisted, in a greenhouse, of the Control; Dinotefuran + Flutriafol 0.5 L.ha-1 ; Dinotefuran + Flutriafol 1.0 L.ha-1 ; Dinotefuran + Flutriafol 2.0 L.ha-1 ; Dinotefuran + Flutriafol 4.0 L.ha-1 ; Thiamethoxan + Cyproconazole 1.0 kg.ha-1 and Imidacloprid + Triadimenol 5.0 L.ha-1 . In seedlings, the rust incidence, morphological characters (height, diameter, and dry weight of the leaves, stem, and root), Soil Plant Analysis Development index (SPAD), and physiological characters using Infrared Gas Analyzer (IRGA) were evaluated. In the field, the treatments were the Control; Dinotefuran + Flutriafol 2.0 L.ha-1 ; Thiamethoxan + Cyproconazole 1.0 kg.ha-1 ; Imidacloprid + Triadimenol 5.0 L.ha-1 , and Imidacloprid + Flutriafol 2.0 L.ha-1 . The rust incidence, defoliation and productivity were measured. In conclusion, the tank mix with fungicides containing Cyproconazole and/or Azoxystrobin mixed with the copper and foliar fertilizers negatively compromised the control efficiency of the coffee rust, reducing leafing. The pH and electrical conductivity changed when the fungicides Cyproconazole and Azoxystrobin were mixed with foliar fertilizer and copper hydroxide. The pH decreased and the electrical conductivity increased in the mix with foliar fertilizer, while the pH increased and the electrical conductivity remained constant when using copper hydroxide. All the fungicides controlled coffee rust under greenhouse conditions. In the case of the soil applications, the treatment with Dinotefuran + Flutriafol at a dose of 2.0 L.ha-1 provided greater height and weight to the seedlings. In the field, all treatments reduced the coffee rust incidence when compared to the control treatment. The treatment with Dinotefuran + Flutriafol at a dose of 2.0 L.ha-1 maintained the lowest incidence of the disease in both harvests and the highest leafing and productivity in the second harvest. There were no phytotoxicity symptoms.